Development Model Micro, Small and Medium Enterprise - Delima Sari Lubis; Zulaika Matondang (AL-FALAH : Journal of Islamic Economics, 2021)
Purpose: Analyzing problems about the factors that influence the development of SMEs in Mandailing Natal. Finding the right model to develop MSMEs in Mandailing Natal.Design/Method/Approach: This research using a qualitative-quantitative approach, with the Analytic method Network Processing (ANP).Findings: The factors that influence the development of MSMEs in Mandailing Natal Regency are human resources, community culture, business management, regulation, competitiveness, capital, and marketing.Originality/Values: Appropriate model to develop MSME in Mandailing Natal district is One Village One Product (OVOP) model based on triple Helix and application of Triple-T Technology Revolution.